2010
DOI: 10.1186/1471-2458-10-s1-s5
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening public health surveillance and response using the health systems strengthening agenda in developing countries

Abstract: There is increased interest in strengthening health systems for developing countries. However, at present, there is common uncertainty about how to accomplish this task. Specifically, several nations are faced with an immense challenge of revamping an entire system. To accomplish this, it is essential to first identify the components of the system that require modification. The World Health Organization (WHO) has proposed health system building blocks, which are now widely recognized as essential components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
86
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 10 publications
6
86
0
1
Order By: Relevance
“…EVD surveillance support functions and response preparedness The findings from this study demonstrate that supervision for surveillance at the district or hospital is rather irregular and also not for Ebola, which supports previous findings (13,14). Although there is some improvement in the training and employment of disease control officers, they remain inefficient and ineffective.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…EVD surveillance support functions and response preparedness The findings from this study demonstrate that supervision for surveillance at the district or hospital is rather irregular and also not for Ebola, which supports previous findings (13,14). Although there is some improvement in the training and employment of disease control officers, they remain inefficient and ineffective.…”
Section: Discussionsupporting
confidence: 76%
“…Largely, it revealed challenges regarding reliability of clinically diagnosed data, accuracy, staff competencies, and commitment. The reported challenges with the rumoured EVD cases are likely attributable to negative attitudes of staff, lack of commitment, fear and panic, lack of PPE, and general lack of skills and competency among health workers, as previously reported in SSA countries (11,13). Previous studies in northern Ghana indicated that IDSR strategy has contributed to increased surveillance report submission as well as analysis of surveillance data (20).…”
Section: Discussionmentioning
confidence: 71%
“…It should be noted that leptospirosis diagnosis in Jamaica is primarily carried out by the veterinary services of the Ministry of Agriculture and that Jamaica's healthcare system could be improved by integrating testing for both leptospirosis and dengue in the same laboratory. 34 It was reported that the malaria epidemic was limited to western Kingston and was controlled and it was not unclear if positive IgG status represented antibodies from persons who were already free of malaria. 30 As Jamaica moves to re-establish its malaria-free status, serology may play an important role in highlighting geographic regions and at risk groups for malaria.…”
Section: Discussionmentioning
confidence: 99%
“…A similar age-prevalence pattern was seen in the 2005 epidemic in Singapore that occurred after successful control of dengue over many years. 34,35,36 In the case of malaria, the Jamaican population is likely to be uniformly immunologically naive and high prevalence at the extremes of age may be associated with mosquito biting rates. The prevalence of Leptospira IgM in suspected dengue cases in the inter-epidemic period of 2002-2007 was reported at 2.5%, 11 whereas the current estimate of 6.0% shows a clear epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, they are founding the framework of centralized quality systems at the national level, 4 with the overall goal of ensuring quality of testing at all laboratories levels. Thus, many countries in subSaharan Africa have allocated resources to expand national external quality assurance (EQA) schemes, mainly through panel testing for different analytes.…”
mentioning
confidence: 99%